(untitled) (Revista de Ciências Agroveterinárias, 2024)
The doses of P to be applied in the corn crop are commonly high due to the low use of the nutrient due to its adsorption to the soil. The objective of this study was to evaluate the use of the phosphate solubilizing bacteria Bacillus megaterium and Bacillus subtilis, and the mycorrhizal fungus Rhizophagus intraradices, as well as the interaction between them, and the possibility of reducing phosphate fertilization in corn. The experimental design was in randomized blocks, in a 4x3 factorial, with factor A composed of different P-solubilizing microorganisms (mycorrhizae and BiomaPhos®) and factor B composed of different doses of P (100, 75 and 50% of the recommended dose). The reduction of P doses, without the use of inoculants, resulted in lower leaf area and chlorophyll content, but no significant effect was observed on plant height. In the yield components number of grains per cob, thousand grain weight and yield, inoculation compensated for the dose reduction. The application of 50% of the P dose together with the inoculation of bacteria was the treatment with the highest gross margin, being viable for the reduction of mineral fertilization.